Peran Koperasi Karyawan Dalam Meningkatkan Kesejahteraan Karyawan dan Sebagai Mitra Strategis Perusahaan - Deddy Supriyadi (Coopetition : Jurnal Ilmiah Manajemen, 2022)
Theoretically, cooperatives have characteristics that have the potential to become advantages as business entities that can play an important role in community economic empowerment. Cooperatives have ideal values ​​and principles as a business entity. Cooperatives also have potential advantages that can make them efficient, a strong bargaining position, a more certain market, so that cooperatives have a better competitive advantage compared to their own businesses. However, the fact is that there are cooperatives that are successful and many that are not. One of the employee cooperatives which is quite large and is known as a successful employee cooperative is the employee cooperative of PT. Biofarma (K2BF). The strategic business units made by K2BF are proven to provide direct and indirect economic benefits to its members. In addition, K2BF can also play a good role as a strategic partner of PT. Biofarma that provides mutual benefits. The success of K2BF in improving the welfare of its members and the role of K2BF as a strategic partner of the company is interesting to study as a best practice.